1980
DOI: 10.1185/03007998009109460
|View full text |Cite
|
Sign up to set email alerts
|

Experience with labetalol in essential hypertension

Abstract: A study was carried out in 73 patients with mild or moderate hypertension to assess the effectiveness of treatment with labetalol. After a 2 to 4-week period on placebo, patients received 200 mg labetalol daily for 4 weeks, after which time dosage was doubled if the blood pressure was not satisfactorily controlled. Treatment was continued for a further 4 weeks and was followed by another period on placebo. Pre-treatment levels of 157/99 mmHg were significantly reduced after 2 weeks, and after 4 weeks the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1982
1982

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, two studies reported a significant reduction in resting heart rate. In one, a decrease of 11 beats/min after 2 weeks was measured (P < 0.001) but this was not sustained thereafter (Tuomilehto, 1980). In the other a decrease of 10 beats/min after 4 weeks occurred (P < 0.001), but there was no dose-response relationship (Kane et al, 1976).…”
Section: Comparative Studiesmentioning
confidence: 99%
“…However, two studies reported a significant reduction in resting heart rate. In one, a decrease of 11 beats/min after 2 weeks was measured (P < 0.001) but this was not sustained thereafter (Tuomilehto, 1980). In the other a decrease of 10 beats/min after 4 weeks occurred (P < 0.001), but there was no dose-response relationship (Kane et al, 1976).…”
Section: Comparative Studiesmentioning
confidence: 99%